2011
DOI: 10.1073/pnas.1118276108
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and stability in bird guilds across tropical countryside

Abstract: The consequences of biodiversity decline in intensified agricultural landscapes hinge on surviving biotic assemblages. Maintaining crucial ecosystem processes and services requires resilience to natural and anthropogenic disturbances. However, the resilience and stability of surviving biological communities remain poorly quantified. From a 10-y dataset comprising 2,880 bird censuses across a land-use gradient, we present three key findings concerning the resilience and stability of Costa Rican bird communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 55 publications
7
112
0
Order By: Relevance
“…In comparison to forest, agricultural habitats are less stable (26) and more regularly disturbed (e.g., pruned, harvested, and replanted). These attributes could preclude sustained competition (27) and favor related species with traits that allow them to persist in agriculture's novel and variable conditions (Fig.…”
Section: Research | Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to forest, agricultural habitats are less stable (26) and more regularly disturbed (e.g., pruned, harvested, and replanted). These attributes could preclude sustained competition (27) and favor related species with traits that allow them to persist in agriculture's novel and variable conditions (Fig.…”
Section: Research | Reportsmentioning
confidence: 99%
“…S1 to S3 Tables S1 to S6 References (21)(22)(23)(24)(25)(26)(27) Habitat conversion is the primary driver of biodiversity loss, yet little is known about how it is restructuring the tree of life by favoring some lineages over others. We combined a complete avian phylogeny with 12 years of Costa Rican bird surveys (118,127 detections across 487 species) sampled in three land uses: forest reserves, diversified agricultural systems, and intensive monocultures.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…89 There has been much semantic and theoretical treatment of the resilience concept, but 90 here we are concerned with identifying metrics for real world applications. An ecological 91 system can be defined by the species composition at any point in time [26] and there is a 92 rich ecological literature, both theoretical and experimental, that focusses on the stability of 93 communities [16,[27][28][29] with potential relevance to resilience. Of course, the species in a 94 community are essential to the provision of many ecosystem functions which are the 95 biological foundation of ecosystem services [3].…”
mentioning
confidence: 99%
“…For example, Verhulst et al [10] found that intensive conventional management of vineyards (high input of external agrochemicals) significantly decreased bird richness, compared with an abandoned vineyard. A long-term study in Costa Rica showed that low intensity management in agroecosystems (e.g., polycultures with high structural diversity) can provide higher resilience and stability of the bird community than high intensity agricultural management [11]. Moorcroft et al [12] found that the abundance of some granivorous species of conservation concern were associated with high amounts of weed seed and a larger proportion of bare soil.…”
Section: Introductionmentioning
confidence: 99%